Clinical Evaluation of RoC Sun Protection Cream SPF44 in Photosensitive Diseases - Matsunaga, Kayoko; Miyachi, Yoshiki; Oishi, Shigeko; Horio, Takeshi; Hashimoto, Hiroko; Ishikawa, Osamu; Ueda, Hiroshi; Washimi, Yasuko; Funasaka, Youko; Kamide, Ryoichi; Ichihashi, Masamitsu; Amano, Hiroo (Skin research, 1999)
RoC Sun Protection Cream SPF44 (supplied by Johnson & Johnson K. K.) was applied to 33 photosensitive subjects who consulted with dermatologists between June 1 and Oct. 31, 1998. This sunscreen product obtains SPF44 and PA++ by dispersion agents and also contains ginkgo biloba and β-glucan (for the inhibition of free radical formation). The 4 and 8 week-tests results showed: 1) an improvement ratio of 69% (20 of 29 cases); 2) a ratio including moderately to remarkably improved cases of 96.6% (28 of 29 cases); and 3) an improvement ratio of 100% in cases with polymorphous light eruption. Moreover, there were no side effects in all cases. These results suggest that this sunscreen product could be applied with excellent efficacy and safety to photosensitive patients and also to healthy people to protect their skin from ultraviolet irradiation.